Academic Achievement Differences by Student Mobility: An Analysis of Texas Grade 8 Student Performance (Global Journal of Human-Social Science, 2017)
Differences in reading, mathematics, and science achievement of Grade 8 students as a function of mobility were examined with and without controls for economic status in this investigation. Data were obtained from the Texas Education Agency Public Education Information Management System for the 2003-2004 through the 2007-2008 school years. Statistically significant differences were revealed in reading, mathematics, and science test scores as a function of student mobility, both when controlling for and not controlling for economic status. Mobile students had statistically significantly lower reading and mathematics test scores than did non-mobile students for all 6 school years. Science scores were statistically significantly lower for all three years for which data were available. Implications for policy and practice and suggestions for future research were made.
Keywords: mobility; academic achievement; poverty; grade 8; texas